Kinetic analysis of the accumulation of a half-sandwich organo-osmium pro-drug in cancer cells. Issue 10 (17th September 2019) - Ballesta, Annabelle; Billy, Frédérique; Coverdale, James P. C.; Song, Ji-Inn; Sanchez-Cano, Carlos; Romero-Canelón, Isolda; Sadler, Peter J.
Abstract : Interdisciplinary study of the cellular transport and metabolism of the organo-osmium complex FY26 in cancer cells towards its clinical development. Abstract : The organo-osmium half-sandwich complex [(η 6 - p -cymene)Os(Ph-azopyridine-NMe2 )I] + (FY26 ) exhibits potent antiproliferative activity towards cancer cells and is active in vivo . The complex is relatively inert, but rapidly activated in cells by displacement of coordinated iodide. Here, we study time-dependent accumulation of FY26 in A2780 human ovarian cancer cells at various temperatures in comparison with the chlorido metabolite [(η 6 - p -cymene)Os(Ph-azopyridine-NMe2 )Cl] + (FY25 ). Mathematical models described the time evolution of FY26 and FY25 intracellular and extracellular concentrations taking into account both cellular transport (influx and efflux) and the intracellular conversion of FY26 to FY25 . Uptake of iodide complex FY26 at 37 °C was 17× faster than that of chloride complex FY25, and efflux 1.4× faster. Osmium accumulation decreased markedly after 24 h of exposure. Modelling revealed that this phenomenon could be explained by complex-induced reduction of osmium uptake, rather than by a model involving enhanced osmium efflux. The intracellular osmium concentration threshold above which reduction in drug uptake was triggered was estimated as 20.8 μM (95% confidence interval [16.5, 30]). These studies provide important new insight into the dynamics of transport of this organometallic anticancer drug candidate.